PENGARUH PERPUTARAN PERSEDIAAN, PERPUTARAN PIUTANG, PENJUALAN BERSIH, HUTANG USAHA TERHADAP LABA BERSIH PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI 2013-2016 - Alex Budi Simangunsong; Catarina Panjaitan; Ester Hasugian; Annisa Nauli Sinaga; Thomas Firdaus Hutahaen (Jurnal Akrab Juara, 2019)
The purpose of this study is to examine and analyze the effect of inventory turnover, receivable turnover, net sales and trade payables on net income in Manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2013-2016. The research method used is descriptive quantitative, this research is causal / clausal. In this study, data collection was carried out through documentation studies. The study uses types and secondary data sources. Based on the results of this study inventory turnover, accounts receivable turnover, net sales and trade payables simultaneously have a positive and significant effect on net income in the Manufacturing companies listed on the Stock Exchange for the period 2013-2016. The conclusions in this study are, accounts receivable turnover, net sales and business debt partially have a positive and significant effect on net income in the BEI listed Manufacturing companies in the period 2013-2016, while the inventory turnover value partially has no effect and is not significant to net income at Manufacturing companies listed on the Indonesia Stock Exchange for the period 2013-2016.